(untitled) (Research, Society and Development, 2022)
Introduction: Chronic kidney disease (CKD) has impacted the health of an increasing number of individuals. Among the main negative impacts are the change in nutritional status (NS) and increased prevalence of anemia. Objective: To associate biochemical parameters with EN of individuals with CKD undergoing hemodialysis (HD). Methods: A cross-sectional and quantitative study was performed at a reference clinic in the hemodialysis treatment. A socioeconomic, anthropometric and biochemical data was collected from 75 individuals with CKD. Results: When evaluating ferritin and transferrin saturation index, 45 individuals (60%) and 55 individuals (73.5%), respectively, were above the recommended range. There was a positive correlation of hemoglobin (Hb) with the anthropometric data body mass index (BMI) (p = 0.013), arm circumference (AC) (p = 0.041) and arm muscle area (AMA) (p = 0.044). The parameters of the BMI and AC were in the classification of eutrophy, and the AMA was classified in the average. The Hb parameter of 74.7% individuals was below the recommended level. Posterior urea correlated significantly with ferritin (p = -, 337) and interdialytic weight gain (IWG) (p = 0.268). Conclusions: After the association of the anthropometric and biochemical parameters with the NS of the individuals with CKD submitted to HD, it was possible to observe that there was a higher prevalence of eutrophic individuals, based on the detailed anthropometric evaluation leading in consideration of its muscular and adipose compartment. Prevalence of the diagnosis of normocitic and normocromic anemia occurred on hematological examinations.